Diseño de un equipo de experimentación del fenómeno de cavitación en bombas y tuberías, para un laboratorio de mecánica de fluidos (2021)
This project was developed with the aim of designing a laboratory equipment for academic application that allows studying the phenomenon of cavitation in pumps and pipes. For the development of the project, the most popular equipment that exists in the international market was studied; determining its operating parameters and functional mode, in order to establish the design parameters for this project. The team was focused on allowing as many experiments as possible, allowing the manipulation of variables associated with cavitation, developing a novel proposal and applying real materials.